Neutral intramolecular hydrogen-bonded bases - Tian, Zhixin (Array, 2009)
Summary: B3LYP/aug-cc-pVDZ computations were carried out on polyamines with up to seven amino groups. The gas-phase proton affinities of these compounds are 219.6 (1-BuNH2), 238.6 (H2NCH2CH2CH2CH2NH2), 252.8 [(H2NCH2CH2CH2)2CHNH2], 261.3 [(H2NCH2CH2CH2)2CNH2 (1)], and 288.5 kcal mol−1 [(H2NCH2CH2CH(NH2)CH2CH2)2CNH2]. These results indicate that the tetraamine is near the top of the basicity scale and the heptaamine is more basic than any neutral organic compound which has been measured to date. A gas-phase equilibrium acidity determination between 1 and DBU also was carried out, and PA(1) = 256.2 ± 2.1 kcal mol−1 was obtained. This demonstrates that multiple intramolecular hydrogen bonds can greatly increase basicities, and represents a new motif for designing super bases